Research of the Degradation Process of Reinforced Concrete Structures. Issue 6 (March 2021) - Varlamov, A A; Rimshin, V I; Davydov, A; Minnatov, A R; Kurbatov, A M
Abstract: The various impact on the durability of concrete and reinforced concrete structures is determined. Three groups of factors are identified that affect the assessment of the durability of reinforced concrete: a) elastic, b) strength, c) crack strength. Based on the analysis, the determining influence of the crack strength factor on concrete degradation was identified. A new method is proposed based on the analysis of existing methods for determining the characteristics of concrete crack strength. The method allows evaluating the crack strength (fracture toughness) of concrete and reinforced concrete structures in any of their conditions. (A method is proposed and a description of samples for implementing the method is given.) Standard formulas were used to evaluate characteristics of crack strength based on prismatic specimens extracted from concrete. Comparative tests of samples were carried out according to the known and proposed method. The obtained characteristics are used to assess the condition and durability of buildings and structures.